AB0075 Intraarterial injection of human adipose-derived mesenchymal stem cells (HAD-MSCS) attenuates inflammation in acute arthritis model. (12th June 2018) - Medina, J.P.; Pérez-Baos, S.; Naredo, E.; López-Reyes, A.; Herrero-Beaumont, G.; Largo, R.
Abstract : Background: MSC are a potential therapeutic approach for the treatment of inflammatory diseases. Their anti-inflammatory role in both local and systemic diseases has been demonstrated in different experimental models and human diseases. Gouty arthritis is a systemic disease characterised by deposition of monosodium urate (MSU) crystals in soft tissues and joints. Frustrated phagocytosis of MSU crystals by resident leukocytes leads to NLRP3 inflammasome activation and subsequent amplification of inflammatory response resulting in severe tissue damage. MSCs are able to attenuate inflammatory response through different mechanisms, including NLRP3 inflammasome inhibition. Thus, MSCs could be a promising therapy for the attenuation of acute flares in gouty arthritis Objectives: To study the antiinflammatory effect of hAD-MSCs in an acute gouty arthritis model Methods: Acute gout flare was induced in 15 NZ rabbits by intra-articular injection of MSU crystals in both knees. 7 of these rabbits received a single dose of 2, 5 × 10 6  hAD-MSCs/kg, administered through the right femoral artery 1 hour after MSU injection (MSU+MSC group), while 8 animales were not treated (MSU group) This route of administration allowed the study of the effect of a direct MSC administration in the right knee synovial membrane (SM) in comparison to the contralateral knee, which received the cells after their vascular distribution through the organism. Inflammation was followed up measuring knee swelling and serum CRP. 4 healthy rabbits were simultaneously followed (Ctrl group). Animals were sacrificed 72 hour after MSU injections and SM were collected for further studies Results: hAD-MSCs were able to attenuate joint swelling in both knees 24 hour after MSU injections, inducing a decrease in knee perimeter. Additionally, a significant decrease in serum CRP after 24 hour was observed in the treated group (Ctrl 73±51; MSU 818±238*; MSU+MSC 270±241 mg/ml*#; p<0.05 *vs. Ctrl; # vs. MSU). Histopathological analysis showed that hAD-MSCs were able to significantly diminish SM inflammation after 72 hours of MSU injection (Krenn Score: Ctrl 0.2±0.4; MSU, 5.6±2.3*, MSU+MSC 3.4±1.2*#). SM vascularisation was reduced in treated animal (%CD31 +staining: Ctrl 0.5±0.2; MSU 0.8±0.2*; MSU+MSC 0.6%±0.2%#). hAD-MSC treatment also evoked a significant reduction of the inflammasome components in the SM: pro-IL1β (Ctrl 0.9±0.2; MSU 1.5±0.5*; MSU+MSC 1.1±0.2*#), pro-caspase-1 (Ctrl 1±0.6; MSU 3.5±3.1*; MSU+MSC 1.4±0.5*#), NALP3 (Ctrl 1±0.3; MSU 2.9±2.1*; MSU+MSC 1.4±0.7*#). The synthesis of the pro-inflammatory cytokines COX-2 (Ctrl 0.9±0.1; MSU 4.2±3.3*; MSU+MSC 2.1±1.4*#) and TNFα (Ctrl 0.9±0.3; MSU 1.3±0.3*; MSU+MSC 0.9±0.2*#) were also reduced in the MSU+MSC animals, while TGFβ (Ctrl 0.9±0.2; MSU 0.7±0.2*; MSU+MSC 1.3±0.3*#) and IL10 (Ctrl 1.1±0.5; MSU 1.1±0.7*; MSU+MSC 1.8±0.5*#) were increased in comparison to MSU group. There were no differences between the direct and the indirect treatment, since both right and left SMs were equally damaged Conclusions: Our data showed that a single dose of hAD-MSCs is able to modulate the inflammatory response in an acute gouty arthritis model in rabbit. Therefore, it is a promising therapeutic approach to attenuate gout flares, especially in patients with different comorbidities that complicate a conventional treatment Disclosure of Interest: None declared